In situ-forming click-crosslinked gelatin based hydrogels for 3D culture of thymic epithelial cells. (24th May 2016) - Truong, Vinh X.; Hun, Michael L.; Li, Fanyi; Chidgey, Ann P.; Forsythe, John S.
Abstract : In situ -forming gelatin based hydrogels, which are crosslinked using an efficient nitrile oxide-norbornene click reaction, provide a suitable 3D culture environment for thymic epithelial cells. Abstract : Hydrogels prepared from naturally derived gelatin can provide a suitable environment for cell attachment and growth, making them favourable materials in tissue engineering. However, physically crosslinked gelatin hydrogels are not stable under physiological conditions while chemical crosslinking of gelatin by radical polymerization may be harmful to cells. In this study, we attached the norbornene functional group to gelatin, which was subsequently crosslinked with a polyethylene glycol (PEG) linker via the nitrile oxide-norbornene click reaction. The rapid crosslinking process allows the hydrogel to be formed within minutes of mixing the polymer solutions under physiological conditions, allowing the gels to be used as injectable materials. The hydrogels properties including mechanical strength, swelling and degradation, can be tuned by changing either the ratio of the reacting groups or the total concentration of the polymer precursors. Murine embryonic fibroblastic cells cultured in soft gels (2 wt% of gelatin and 1 wt% of PEG linker) demonstrated high cell viability as well as similar phenotypic profiles (PDGFRα and MTS15) to Matrigel cultures over 5 days. Thymic epithelial cell and fibroblast co-cultures produced epithelial colonies in these gels following 7 days incubation. These studies demonstrate that gelatin based hydrogels, prepared using "click" crosslinking, provide a robust cell culture platform with retained benefits of the gelatin material, and are therefore suitable for use in various tissue engineering applications.